Campylobacter in aquatic and terrestrial mammals is driven by life traits: A systematic review and meta-analysis - Brooks, Michael R.; Medley, Sarah; Ponder, Monica; Alexander, Kathleen A. (Frontiers in Ecology and Evolution, 2023)
Campylobacter spp. infections are responsible for significant diarrheal disease burden across the global, with prevalence thought to be increasing. Although wild avian species have been studied as reservoirs of Campylobacter spp., our understanding of the role of wild mammalian species in disease transmission and persistence is limited. Host factors influencing infection dynamics in wild mammals have been neglected, particularly life traits, and the role of these factors in zoonotic spillover risk is largely unknown. Here, we conducted a systematic literature review, identifying mammalian species that had been tested for Campylobacter spp. infections (direct and culture based). We used logistic regression to evaluate the relationship between the detection of Campylobacter spp. in feces and host life traits (urban association, trophic level, and sociality). Results suggest that C. jejuni transmission is associated with urban living and trophic level. The probability of carriage was highest in urban-associated species (p=0.0216) and the most informative model included trophic level. In contrast, C. coli carriage appears to be strongly influenced by sociality (p=0.0160) with trophic level still being important. Detection of Campylobacter organisms at the genus level, however, was only associated with trophic level (p=0.0103), highlighting the importance of this trait in exposure dynamics across host and Campylobater pathogen systems. While many challenges remain in the detection and characterization of Camploybacter spp, these results suggest that host life traits may have important influence on pathogen exposure and transmission dynamics, providing a useful starting point for more directed surveillance approaches.